2021
DOI: 10.1177/09670335211007673
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared spectroscopy of plantation forest soil nutrients in Sabah, Malaysia, and the potential for microsite assessment

Abstract: Knowledge of soil physical and chemical properties is vital to the optimal growing performance of agricultural crops, including plantation forest trees. Near infrared (NIR) spectroscopy has been shown to be a tool that enables rapid and low-cost assessment of soils, however its use in forest plantations has been slow to develop. This study shows the development of calibrations for total organic carbon, total nitrogen and soil pH using a handheld NIR spectrometer for soils at three sites in Sabah, Malaysia. Soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Also, this is consistent with results of Liu et al, 52 who found that stratifying samples by soil type improved prediction of SOC content. Moreover, Ahmad Jani et al 93 improved predictions of soil total organic carbon by stratifying samples of A and B horizons independently. In addition, Stenberg et al 18 stated that overall variability in soil properties would influence prediction accuracy to a small extent.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this is consistent with results of Liu et al, 52 who found that stratifying samples by soil type improved prediction of SOC content. Moreover, Ahmad Jani et al 93 improved predictions of soil total organic carbon by stratifying samples of A and B horizons independently. In addition, Stenberg et al 18 stated that overall variability in soil properties would influence prediction accuracy to a small extent.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to Vis-NIR spectrophotometers, compact NIR instruments operate in a shorter range of the electromagnetic spectrum, [11][12][13] but in terms of performance in SOC determination, the current literature shows that models based on these instruments can present excellent accuracy. 10,[14][15][16] However, the performance of compact NIR spectrophotometers in SOC determination using large and heterogeneous data sets has seldom been studied 17 and, until now, methodological aspects such as soil sample preparation for using these instruments have not yet been addressed extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Human initial afforestation is mainly in order to production needs, as a part of the agricultural production, with the progress of social productivity, timber demand increasing, under the natural state of forest resource components are insufficient to satisfy the human production and life, people began planting plantation, planted forest ecological level and function is becoming more and more attention [20]. Therefore, this article is based on C/S architecture and the J2EE platform, in the Struts framework with the business model -user interface -controller programming model, under the support of construct artificial planting forest ecological management system, through the synergy evaluation module, the ecological function value of the principal component comprehensive analysis module and the depth of the extreme learning machine learning algorithm of planted forests demand forecast module, Various indicators and factors affecting the ecological function of planted forests were evaluated and analyzed in order to better understand the biodiversity of planted forests and its regulation approaches and mechanisms on ecological function and to provide scientific basis and technical means for guiding the ecological management and sustainable management of planted forests [21].…”
Section: Introductionmentioning
confidence: 99%